(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article discusses General Mikhail Chernyaev’s activities during the Russian Empire’s conquest of the Central Asian khanates, his military achievements, and their impact on the region’s political landscape. In particular, the analysis focuses on his capture of Tashkent in 1865, his campaigns against the Khanate of Kokand, and his role in the establishment of the Turkestan Governor-Generalship. Additionally, the reasons and outcomes of Russia’s expansion into Central Asia, the khanates’ inability to resist, and the oppression and economic pressure on the local population are highlighted.